Traversing Doctoral Borderlands: Black doctoral students' experiences of identity construction in South Africa - Hwami, Rudo Fortunate (Rhodes University, Faculty of Humanities, Department of Political and International Studies)
Doctoral studies are described as a process of formation and becoming. This is an in-between space between unknowing and knowing, within and without the ivory tower of academia. In this in-between space the doctoral candidate takes the role of a novice and apprentice unlearning the student/unknowing past and learning to become a professional in academia. This project utilises the borderlands theory to understand the experiences of doctoral students as they undergo the process of becoming and intellectual identity formation. Whilst 'journey' and other metaphors that have been used to understand doctoral student experiences capture the process of becoming as a progression through the liminal stages "“ proposal, literature review, context, writing, reading etc. These stages presuppose temporality of being leading to stasis/completion. I argue that such conceptualisation of doctoral studies, although useful, depict one side of the story and provide a limited, monolithic, and homogenising understanding of the spatial configurations of doctoral space and intellectual identity formation. The dominant discourses of doctoral conceived and perceived space, liminal stages and understanding of doctoral student experiences, mask the more latent and intimate liminal stages of intellectual identity formation. Drawing from borderlands theory, I firstly argue for a holistic approach to understanding the spatiality of doctorate studies. Secondly, I argue that liminality is an everyday process integral to human existence where one is always in a state of ideological transition. An important state of liminality is the awareness of 'Self' in perpetual motion, caught between two worlds dominated/dominator and two ideologies of oppression/resistance. If this side of liminality is not made visible, institutional spaces, such as the doctorate, privileged with the power to disseminate and position onto-epistemologies as universal can be used to reproduce and reinforce exclusionary onto-epistemologies that subsequently impact intellectual identity formation. Using Lefebvre's (1991) rhythmanalysis method, I use student experiences not as mere data for analysis, but as an act of envisioning, reinventing and coknowledge production to propose borderlands as a new metaphor to study doctoral spatial realities and the experiences of the students that traverse through it.
Keywords: Doctoral students -- South Africa; College students, Black -- South Africa; Marginality, Social -- South Africa; Public spaces Social aspects; Culture Social aspects; Rhythm; Identity (Psychology); Borderlands Theory